Annulipalpia (Insecta: Trichoptera) from the state of Espírito Santo, brazil - Silva, Patrik Barcelos e; Pes, A. M.; Salles, Frederico Falcaõ (Check List, 2012)
In order to access and integrate the knowledge regarding the diversity of the suborder Annulipalpia (Insecta: Trichoptera) from the state of Espírito Santo, southeastern Brazil, we present a preliminary list of this group based on literature and on adults collected from 26 different sites in the state. Prior to this study only 11 species of Annulipalpia, belonging to six genera and two families were reported from the state. Based on the adults collected during this study the number of taxa increased considerably to 48 species, 15 genera and five families. Ten species could not be identified and probably are new to science. With the performance of new collections and with the increase in number of sampling points, the number of species of Annulipalpia as well of Trichoptera can still grow considerably. © 2012 Check List and Authors.
Keywords: Annulipalpia; Insecta; Trichoptera